2007
DOI: 10.1002/chin.200721036
|View full text |Cite
|
Sign up to set email alerts
|

1,8‐Diazabicyclo[5.4.0]undec‐7‐ene (DBU)‐Promoted Efficient and Versatile aza‐Michael Addition.

Abstract: Amination O 0268 1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU)-Promoted Efficient and Versatile aza-Michael Addition. -Various nitrogen nucleophiles such as primary and acyclic and cyclic secondary amines are efficiently introduced to α,β-unsaturated carbonyl compounds in the presence of 0.5 equiv. DBU. Compared to other tertiary amines, it is uniquely effective. Two other representative nucleophiles, a thiol and a phosphite, undergo the corresponding hetero-Michael addition reaction with excellent yields. -(YEOM, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…In solution, it was found that 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) is a suitable catalyst for the forward aza-Michael reaction 24 and at the same time also catalyses the retro reaction 25 (see Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In solution, it was found that 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) is a suitable catalyst for the forward aza-Michael reaction 24 and at the same time also catalyses the retro reaction 25 (see Supplementary Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Benzyl (2 S ,4 R )‐4‐{[ tert ‐Butyl(dimethyl)silyl]oxy}‐2‐({(2 S )‐1‐[(2‐cyanoethyl)(prop‐2‐en‐1‐yl)amino]‐1‐oxo‐4‐phenylbutan‐2‐yl}carbamoyl)pyrrolidine‐1‐carboxylate ( 22c ) was synthesized following the General Procedure from 17a (162 mg, 0.3 mmol) and 21c , obtained according to (40 mg, 0.36 mmol), affording 157 mg (82.7%) of 22c as syrup. false[italicαfalse]normalD27.4 = −36.8 ( c = 0.5, CHCl 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The aza-Michael reaction has been accomplished with several additives to increase its efficiency. Among them are variety of Lewis acids such as InCl 3 , [3] Bi(NO 3 ) 2 and Bi(OTf) 2 , [4] PdCl 2 (MeCN) 2 , [5] Yb(OTf) 2 , [6] LiClO 4 , [7] FeCl 3 , [8] SmI 2 , [9] ceric ammonium nitrate, [10] stoichiometric amounts of AlCl 3 =TiCl 4 =SnCl 4 , [11] clay , [12] heterogeneous solid salts , [13] ionic liquids with Cu(acac) 2 or quaternary ammonium salts, [14] b-cyclodextrin, [15] polystyrenesulfonic acid, [16] 1,8-diazabicyclo [5.4.0]-undec-7-ene (DBU), [17] some organic promoters, [18] and sodium dodecylsulfate. [19] The use of these additives and organic solvents along with much higher reaction temperatures do not agree with the main principles of green synthesis.…”
Section: Introductionmentioning
confidence: 99%